Research of data fusion methods of compressed sensing-based orchard monitoring system by wireless sensor networks. (1st January 2013) - Yin, Yan; Wang, Chuanyun; Zhang, Yuejin
A novel data fusion method for monitoring the fruit growth environment is proposed, combining the model based on parameter evaluation method with the compressed sensing technique and taking Gannan navel orange as an example in this paper. The model based on parameter evaluation is used to extract the space-time characteristic information of fruit growth environment. The distributed compressed sensing (CS) technique is used to significantly reduce the amount of data transmission, improve the accuracy of information and prolong the lifecycle of the network. Accordingly, an experiment platform of wireless sensor networks (WSN) is built for sampling accurately the parameters of the fruit growth environment in real-time. A scientific management programme is developed to optimise the fruit growth environment, according to the proposed parameters model. It is helpful for spreading the practical application of wireless sensor networks in the orchard modern management.